Experimental Studies On Effect Of Process Parameters On Tool Wear In Drilling CFRP Composites With Ultrasonic Machine - Mohammed Muslem, Mohammed Bakar (2019)
Hole production was long recognized as the most important process of machining, requiring specialized techniques to achieve optimum cutting conditions. Drilling can be described as a process in which a multi - point tool is used to remove unwanted materials for the desired hole production. However, high production processing and drilling with high cutting speed and feed rate are inherently linked to high heat generation and high cutting temperatures which cause tool wear. CFRP composites used in many applications such as aerospace efficiency, fuel cells, turbo machinery, compressed gas storage and transport, electromagnetic wind turbine shielding materials in automotive energy systems and offshore–deep sea drilling platforms, antistatic due to outstanding properties such as magnetic, low thermal expansion coefficient, high weight-tostrength and weight-to-stiffness ratio and corrosion resistance. High - speed steel (HSS) is the lowest cost drawing material for general purposes and the easiest to find. In this case, submersible reduces the temperature very effectively. A large amount of tool wear appears on the drill bit when the temperature is increased. High temperatures affect both the roundness of the hole or the shape of the chip and the color of the chip. Submersible reduced temperature and improved roundness and also lubricates the tool tip and surface interface. The comparison between parameters and condition has been made to observe the best condition & parameters to increase the tool life.